Rodent models of genetic epilepsy and its association with neurocognitive impairment- a systematic review - Foo, Renee Yan Ni; Chiew, Ian Juin Liang; Arulsamy, Alina; Lee, Vanessa Lin Lin (Frontiers in Pharmacology, 2026)
Epilepsy is a neurological disorder affecting almost 50 million people worldwide, with genetic epilepsy (GE) representing a subset caused by specific gene mutations. While cognitive deficits are frequently reported in epilepsy, the contribution of GE itself remains poorly defined. We conducted a systematic review to evaluate the cognitive and behavioral phenotypes in rodent models of GE, focusing on cognition as the primary outcome and behavior as secondary. Literature searches of PubMed, Ovid MEDLINE, and Scopus identified 16 eligible studies in accordance with Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Across models, rodents with GE commonly exhibited impairments in the neurocognitive and behavioral paradigms. Mutant rodent models were exhibit poorer memory and learning abilities, alongside behavioral abnormalities such as autism spectrum disorder (ASD)-like phenotype, anxiety, and depression. However, the severity and domains of impairment varied across mutations, strains, and developmental stages, reflecting the heterogeneity of GE. Our findings highlight both seizure-driven and gene-driven mechanisms of cognitive impairment and underscore the need for syndrome-specific investigations. Overall, rodent models provide valuable insights into the cognitive comorbidities of GE, but future research requires improved methodological rigor and broader use of complementary models to clarify underlying mechanisms and guide targeted interventions.